Differential interactions of age and sleep deprivation in driving and spatial perception by male drivers in a virtual reality environment - Izullah Faramosh Rashid; af Schulten Anna; Koivisto Mika; Nieminen Valtteri; Luimula Mika; Hämäläinen Heikki (WILEY, 2022)
We determined the effects of age and sleep deprivation on driving and spatial perception in a virtual reality environment. Twenty-two young (mean age: 22 years, range: 18-35) and 23 old (mean age: 71 years, range: 65-79) participants were tested after a normal night of sleep and a night of sleep deprivation. The participants drove a virtual car while responding to uni- and bilateral visual and auditory stimuli. Driving errors (crossing the lane borders), reaction times and accuracy to visual and auditory stimuli, performance in psychological tests, and subjective driving ability and tiredness were measured. Age had no effect on the number of driving errors, whereas sleep deprivation increased significantly especially the number of left lane border crossings. Age increased the number of stimulus detection errors, while sleep deprivation increased the number of errors particularly in the young and in the auditory modality as response omissions. Age and sleep deprivation together increased the number of response omissions in both modalities. Left side stimulus omissions suggest a bias to the right hemispace. The subjective evaluations were consistent with the objective measures. The psychological tests were more sensitive to the effects of age than to those of sleep deprivation. Driving simulation in a virtual reality setting is sensitive in detecting the effects of deteriorating factors on both driving and simultaneous spatial perception.